Ultraviolet curing adhesive and preparation method thereof

By using a specific combination of polyurethane acrylate resin and oligomer, an ultraviolet curing adhesive with high adhesion, good versatility and excellent UV aging resistance was prepared, and the lack of adhesion in the prior art was solved. and poor UV aging resistance.

CN119391356AActive Publication Date: 2025-02-07DONGGUAN CITY BETTERLY NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411687263.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-07
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

When the existing UV adhesive is bonded to the liquid crystal layer, optical polymer layer and coating layer used in the back cover of a smartphone, the adhesive strength is insufficient, the versatility is poor, and the UV aging resistance is poor, which makes it prone to delamination.

Method used

30 parts by weight to 60 parts by weight, 30 parts by weight to 50 parts by weight, 1 part by weight to 5 parts by weight of photoinitiator, 5 parts by weight to 20 parts by weight of special structure oligomer, and coupling agent. The ultraviolet curing adhesive is prepared by mixing and modification technology by combining 1 part to 6 parts by weight and 0 part to 3 parts by weight of the additive.

Benefits of technology

It significantly improves the adhesion between the liquid crystal layer, optical polymer layer or coating layer and plastic film. The conventional adhesion can reach more than 40N after ultraviolet curing, and the adhesion can reach more than 25N after UV aging resistance test. Improves the adhesion and UV aging resistance in the back cover bonding process of smartphones.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005150257360000081
    Figure BDA0005150257360000081
  • Figure BDA0005150257360000091
    Figure BDA0005150257360000091
  • Figure BDA0005150257360000101
    Figure BDA0005150257360000101
Patent Text Reader

Abstract

The invention provides an ultraviolet curing adhesive. The ultraviolet curing adhesive is prepared from the following raw materials in parts by weight: 30-60 parts of urethane acrylate; 30 to 50 parts by weight of a reactive diluent; 1 part by weight to 5 parts by weight of a photoinitiator; 5-20 parts by weight of a special structure oligomer; 1-6 parts by weight of a coupling agent; 0-3 parts by weight of an auxiliary agent; the oligomer with the special structure is selected from one or more of metal polyester acrylate, carboxyl-containing acrylate oligomer and acrylic phosphate. Compared with the prior art, the ultraviolet curing adhesive provided by the invention adopts components with specific contents, realizes better overall interaction, and is strong in product adhesive strength, good in universality and excellent in ultraviolet aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and more specifically, to an ultraviolet light curing adhesive and a preparation method thereof. Background Art

[0002] With the rapid development of smartphone application design, the process of bonding multiple layers of materials is used in the manufacturing of smartphone back covers to obtain gorgeous appearance and texture. Among them, liquid crystal layer, optical polymer layer and coating layer are new materials commonly used in new bonding processes in recent years. However, due to the high degree of polymerization or high density of these materials, most UV adhesives on the market currently have insufficient adhesion to them and poor versatility, and are prone to delamination in subsequent reliability tests, especially UV aging tests.

[0003] At present, patent CN115322732A discloses a UV adhesive for bonding a coating and a diaphragm, which includes 40-80 parts of a main resin, 15-60 parts of an active diluent, 1-5 parts of a photoinitiator, 1-4 parts of a silane coupling agent, and 1-5 parts of an adhesion promoter, by weight. The invention also provides an application method of the UV adhesive for bonding a coating and a diaphragm. The purpose is to solve the problem of weak adhesion between the coating and the diaphragm, and between the coatings; the well-bonded diaphragm can still maintain a high adhesion after high-pressure molding; shorten the waiting time for printing ink, thereby shortening the production cycle of the mobile phone battery cover. The main resin described in the invention is selected from one or more of pure acrylate resin, polyurethane acrylic resin, and polyether acrylic resin. However, in each embodiment, only conventional adhesion and adhesion after high-pressure molding are disclosed, and the problem of insufficient adhesion and delamination after ultraviolet light aging test or water boiling resistance reliability test in the industry is not solved. Summary of the invention

[0004] In view of this, an object of the present invention is to provide a UV-curing adhesive and a preparation method thereof. The UV-curing adhesive provided by the present invention has strong bonding force, good versatility, and excellent UV aging resistance.

[0005] The present invention provides a UV-curable adhesive, which is prepared from raw materials including the following components:

[0006] 30 to 60 parts by weight of polyurethane acrylate;

[0007] 30 to 50 parts by weight of active diluent;

[0008] 1 to 5 parts by weight of photoinitiator;

[0009] 5 to 20 parts by weight of special structure oligomer;

[0010] 1 to 6 parts by weight of coupling agent;

[0011] Auxiliary agent 0 to 3 parts by weight;

[0012] The special structure oligomer is selected from one or more of metal polyester acrylate, carboxyl-containing acrylate oligomer, and acrylic phosphate.

[0013] Preferably, the preparation method of the polyurethane acrylate is specifically as follows:

[0014] IPDI, IBOA, MEHQ and an organic bismuth catalyst are sequentially added into a reaction kettle, and a mixed solution of PTMG3000 and diethylene glycol is added dropwise under stirring, and the dropping speed is adjusted according to the temperature to ensure that the temperature does not exceed 60° C. After the dropping is completed, the temperature is kept at 55° C. to 66° C. for 1 h to 3 h; then NCO is detected, and the reaction target value is reached when NCO is between 0.4 and 0.5, otherwise the reaction is continued; after reaching the reaction target value, HEA is added, and the temperature is raised to 70° C. to 90° C. to start the heat preservation reaction, and after keeping the temperature for 1 h to 3 h, the NCO content is measured every hour, and the reaction is stopped when the NCO content is less than 0.05%, and the discharged material is filtered and packaged to obtain polyurethane acrylate.

[0015] Preferably, the active diluent is selected from one or more of lauryl acrylate, N,N-dimethylacrylamide, cyclotrimethylolpropane formal acrylate, N-vinyl pyrrolidone, ethoxyethoxyethyl acrylate, isobornyl acrylate, and tetrahydrofuran acrylate.

[0016] Preferably, the photoinitiator is selected from one or more of 1-hydroxycyclohexyl phenyl ketone, (2,4,6-trimethylbenzoyl)di(p-tolyl)phosphine oxide, ethyl 2,4,6-trimethylbenzoylphosphonate, and methyl benzoylformate.

[0017] Preferably, the special structure oligomer is metal polyester acrylate, or carboxyl-containing acrylate oligomer, or acrylic acid phosphate, or carboxyl-containing acrylate oligomer and acrylic acid phosphate in a mass ratio of 1:1.

[0018] Preferably, the coupling agent is selected from silane coupling agent and / or epoxy silane oligomer; the silane coupling agent is selected from one or more of γ-methacryloxypropyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 1,3,5-tris(trimethoxysilylpropyl)isocyanurate, N-(3-dimethylaminoethyl)-3-aminopropylmethyldimethoxysilane, N-(piperazineethyl)-3-aminopropylmethyldimethoxysilane; the epoxy silane oligomer is selected from one or more of Maitu MP-200, Aiko Crosile AK200, and Mitsukoshi SY-60.

[0019] Preferably, the auxiliary agent is a light attractant and / or a light stabilizer.

[0020] The present invention also provides a method for preparing the UV-curable adhesive described in the above technical solution, comprising the following steps:

[0021] The photoinitiator and the active diluent are mixed, stirred at a low speed until the photoinitiator is completely dissolved, and then polyurethane acrylate, special structure oligomer, coupling agent and auxiliary agent are added, stirred and heated to 40°C to 60°C, dispersed at a high speed and then filtered to obtain a UV-curing adhesive.

[0022] Preferably, the rotation speed of the low-speed stirring is 100 r / min to 300 r / min.

[0023] Preferably, the rotation speed of the high-speed dispersion is 800 r / min to 1500 r / min.

[0024] The present invention provides a UV-curable adhesive, which is prepared from raw materials including the following components: 30 to 60 parts by weight of polyurethane acrylate; 30 to 50 parts by weight of reactive diluent; 1 to 5 parts by weight of photoinitiator; 5 to 20 parts by weight of special structure oligomer; 1 to 6 parts by weight of coupling agent; 0 to 3 parts by weight of auxiliary agent; the special structure oligomer is selected from one or more of metal polyester acrylate, carboxyl-containing acrylate oligomer, and acrylic acid phosphate. Compared with the prior art, the UV-curable adhesive provided by the present invention adopts specific content components to achieve better overall interaction, and the product has strong adhesion, good versatility, and excellent UV aging resistance.

[0025] In addition, the preparation method provided by the present invention has simple process, mild and easy-to-control conditions, and readily available raw materials with low cost, and has broad application prospects. DETAILED DESCRIPTION

[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The present invention provides a UV-curable adhesive, which is prepared from raw materials including the following components:

[0028] 30 to 60 parts by weight of polyurethane acrylate;

[0029] 30 to 50 parts by weight of active diluent;

[0030] 1 to 5 parts by weight of photoinitiator;

[0031] 5 to 20 parts by weight of special structure oligomer;

[0032] 1 to 6 parts by weight of coupling agent;

[0033] Auxiliary agent 0 to 3 parts by weight;

[0034] The special structure oligomer is selected from one or more of metal polyester acrylate, carboxyl-containing acrylate oligomer, and acrylic phosphate.

[0035] The UV adhesives commonly used in the market have weak adhesion to the liquid crystal layer, optical polymer layer and coating layer used in the back cover of mobile phones, poor versatility, and obvious decrease in adhesion after boiling test or UV aging test, and are prone to delamination. In view of the above technical problems, the present invention synthesizes an oligomer polyurethane acrylate, and through the blending modification of polyurethane acrylate, provides a UV curing adhesive with strong adhesion, good versatility and excellent UV aging resistance.

[0036] In the present invention, the UV-curable adhesive is prepared from raw materials including polyurethane acrylate, reactive diluent, photoinitiator, special structure oligomer, coupling agent and auxiliary agent, preferably prepared from polyurethane acrylate, reactive diluent, photoinitiator, special structure oligomer, coupling agent and auxiliary agent.

[0037] In the present invention, the preparation method of the polyurethane acrylate is preferably as follows:

[0038] IPDI, IBOA, MEHQ and an organic bismuth catalyst are sequentially added into a reaction kettle, and a mixed solution of PTMG3000 and diethylene glycol is added dropwise under stirring, and the dropping speed is adjusted according to the temperature to ensure that the temperature does not exceed 60° C. After the dropping is completed, the temperature is kept at 55° C. to 66° C. for 1 h to 3 h; then NCO is detected, and the reaction target value is reached when NCO is between 0.4 and 0.5, otherwise the reaction is continued; after reaching the reaction target value, HEA is added, and the temperature is raised to 70° C. to 90° C. to start the heat preservation reaction, and after keeping the temperature for 1 h to 3 h, the NCO content is measured every hour, and the reaction is stopped when the NCO content is less than 0.05%, and the discharged material is filtered and packaged to obtain polyurethane acrylate;

[0039] More preferably:

[0040] IPDI, IBOA, MEHQ and an organic bismuth catalyst are sequentially added into a reaction kettle, and a mixed solution of PTMG3000 and diethylene glycol is added dropwise under stirring, and the dropping speed is adjusted according to the temperature to ensure that the temperature does not exceed 60° C. After the dropping is completed, the temperature is kept at 60° C. for 2 hours; then NCO is detected, and the reaction target value is reached when NCO is between 0.4 and 0.5, otherwise the reaction is continued; after reaching the reaction target value, HEA is added, and the temperature is raised to 80° C. to start the insulation reaction. After insulation for 2 hours, the NCO content is measured every hour, and the reaction is stopped when the NCO content is less than 0.05%, and the discharged material is filtered and packaged to obtain polyurethane acrylate.

[0041] The present invention has no particular restrictions on the sources of the IPDI, IBOA, MEHQ (p-hydroxyanisole), organic bismuth catalyst, PTMG3000, diethylene glycol, and HEA, and commercially available products known to those skilled in the art may be used.

[0042] In the present invention, the mass ratio of IPDI, IBOA, MEHQ, organic bismuth catalyst, PTMG3000, diethylene glycol and HEA is preferably (100-200): (750-850): 1: (0.5-1.5): (900-950), (20-40): (20-40).

[0043] In order to improve the adhesion between materials such as liquid crystal layer, optical polymer layer or coating layer and plastic film (PC or PET), the present invention adopts the above-mentioned oligomer polyurethane acrylate resin, which has the characteristics of moderate molecular weight, high transparency, excellent adhesion, good flexibility and stable structural performance; the resin has excellent resistance to outdoor environment and ultraviolet aging, so as to improve the adhesion to high molecular polymer layer, coating layer and plastic film, and the characteristics of stable ultraviolet aging resistance.

[0044] In the present invention, the UV-curable adhesive comprises 30 to 60 parts by weight of polyurethane acrylate, preferably 43 to 50 parts by weight.

[0045] In the present invention, the active diluent is an important component of the UV-curable adhesive. On the one hand, it acts as a diluent to adjust the overall viscosity of the adhesive and increase the wetting effect of the adhesive on the bonding substrate; on the other hand, it has reaction activity and can copolymerize with the oligomer to form a network structure when illuminated, thereby adjusting the photocuring rate of the system and improving the performance of the adhesive. The active diluent is preferably selected from one or more of lauryl acrylate, N,N-dimethylacrylamide, cyclotrimethylolpropane formal acrylate, N-vinyl pyrrolidone, ethoxyethoxyethyl acrylate, isobornyl acrylate, and tetrahydrofuran acrylate, and more preferably one or more of lauryl acrylate, N,N-dimethylacrylamide, cyclotrimethylolpropane formal acrylate, and N-vinyl pyrrolidone. In a preferred embodiment of the present invention, the active diluent is lauryl acrylate, N,N-dimethylacrylamide, and N-vinyl pyrrolidone in a mass ratio of 1:1:2; in another preferred embodiment of the present invention, the active diluent is lauryl acrylate, N-vinyl pyrrolidone, and cyclotrimethylolpropane formal acrylate in a mass ratio of 1.5:1:2; in a preferred embodiment of the present invention, the active diluent is lauryl acrylate, N,N-dimethylacrylamide, and N-vinyl pyrrolidone in a mass ratio of 1.4:0.7:1.5. The present invention has no special restrictions on the source of the active diluent, and the commercially available products of the above-mentioned monofunctional acrylates well known to those skilled in the art can be used.

[0046] In the present invention, the UV-curable adhesive comprises 30 to 50 parts by weight of a reactive diluent, preferably 36 to 45 parts by weight.

[0047] In the present invention, the photoinitiator is preferably selected from one or more of 1-hydroxycyclohexyl phenyl ketone, (2,4,6-trimethylbenzoyl) di(p-tolyl) phosphine oxide, ethyl 2,4,6-trimethylbenzoylphosphonate, and methyl benzoylformate, and more preferably 1-hydroxycyclohexyl phenyl ketone and (2,4,6-trimethylbenzoyl) di(p-tolyl) phosphine oxide in a mass ratio of 1:1. The present invention has no particular restrictions on the source of the photoinitiator, and commercially available products known to those skilled in the art can be used.

[0048] In the present invention, the UV-curable adhesive comprises 1 to 5 parts by weight of a photoinitiator, preferably 3 to 4 parts by weight.

[0049] In the present invention, the special structure oligomer is selected from one or more of metal polyester acrylate, carboxyl acrylate oligomer, and acrylic acid phosphate, preferably metal polyester acrylate, carboxyl acrylate oligomer, acrylic acid phosphate, or carboxyl acrylate oligomer and acrylic acid phosphate in a mass ratio of 1:1. The present invention has no special restrictions on the source of the special structure oligomer, and commercially available products known to those skilled in the art can be used.

[0050] The UV-curable adhesive obtained by the method of blending the above-mentioned specific polyurethane acrylate with the special structure oligomer can form covalent cross-linking through functional groups such as acrylic acid, carboxyl, and hydroxyl groups, and has ionic cross-linking, which can greatly improve the adhesion to substrates such as metal and glass; phosphate ester has a slight phosphating effect on substrates such as metal, which is beneficial to improve the adhesion to the substrate.

[0051] In the present invention, the UV-curable adhesive comprises 5 to 20 parts by weight of a photoinitiator, preferably 5 to 6 parts by weight.

[0052] In the present invention, the coupling agent is preferably selected from silane coupling agents and / or epoxy silane oligomers, more preferably silane coupling agents or epoxy silane oligomers; the silane coupling agent is preferably selected from γ-methacryloxypropyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 1,3,5-tris(trimethoxysilylpropyl)isocyanurate, N-(3-dimethylaminoethyl)-3-aminopropylmethyldimethoxysilane, N-(piperazineethyl)-3-aminopropylmethyldimethoxysilane, one or more; the epoxy silane oligomer is preferably selected from one or more of Maitu MP-200, Aikop CrosileAK200, and Mitsukoshi SY-60. The present invention has no special restrictions on the source of the coupling agent, and commercially available products known to those skilled in the art can be used.

[0053] The present invention modifies the UV-curing adhesive with the above-mentioned silane coupling agent, epoxy silane polymer, etc., which not only increases the intermolecular force of the main resin molecules themselves and improves the cohesive strength of the adhesive, but also increases the bonding between the main resin and the adherend, plays a certain "bridging" role, and improves the bonding performance of the adhesive.

[0054] In the present invention, the UV-curable adhesive comprises 1 to 6 parts by weight of a coupling agent, preferably 2 to 4 parts by weight.

[0055] In the present invention, the auxiliary agent is preferably a light attractant and / or a light stabilizer, more preferably a light attractant or a light stabilizer, such as N-(2-ethoxyphenyl)-N'-(4-isododecylphenyl)-ethylenediamine, hydroxytriazine derivatives, N-(1-acetyl-2,2,6,6-tetramethyl-4-piperidinyl)-2-dodecylsuccinimide, etc. The present invention has no particular restrictions on the source of the auxiliary agent, and commercially available products known to those skilled in the art can be used.

[0056] The invention modifies the ultraviolet light curing adhesive with auxiliary agents such as light absorbers and light stabilizers, thereby effectively inhibiting the aging of polymer materials, delaying the light aging process thereof, and being conducive to ensuring the long-term light stability of the adhesive layer.

[0057] In the present invention, the UV-curable adhesive comprises 0 to 3 parts by weight of an auxiliary agent, preferably 0 to 1 part by weight.

[0058] The invention significantly improves the bonding force between a liquid crystal layer, an optical polymer layer or a coating layer and a plastic film by synthesizing a polyurethane acrylate oligomer and blending and modifying the polyurethane acrylate oligomer with a special structure, a coupling agent, an anti-ultraviolet light aging additive, etc. After ultraviolet light curing, the conventional bonding force between the liquid crystal layer, the optical polymer layer or the coating layer and the plastic film (PC or PET) can reach more than 40N, and the bonding force can reach more than 25N after ultraviolet light aging (72h) test; the invention significantly improves the problems of weak bonding force, poor versatility and easy delamination after ultraviolet aging test between the liquid crystal layer, the optical polymer layer or the coating layer and the plastic film in the lamination manufacturing process of the back cover of a smart phone.

[0059] The present invention also provides a method for preparing the UV-curable adhesive described in the above technical solution, comprising the following steps:

[0060] The photoinitiator and the active diluent are mixed, stirred at a low speed until the photoinitiator is completely dissolved, and then polyurethane acrylate, special structure oligomer, coupling agent and auxiliary agent are added, stirred and heated to 40°C to 60°C, dispersed at a high speed and then filtered to obtain a UV-curing adhesive.

[0061] In the present invention, the photoinitiator, reactive diluent, polyurethane acrylate, special structure oligomer, coupling agent and auxiliary agent are the same as those in the above technical solution, and will not be described in detail here.

[0062] In the present invention, the rotation speed of the low-speed stirring is preferably 100 r / min to 300 r / min, more preferably 150 r / min to 250 r / min; the rotation speed of the high-speed dispersion is preferably 800 r / min to 1500 r / min, more preferably 800 r / min to 1200 r / min.

[0063] In view of the problems of weak adhesion, poor versatility and poor UV aging resistance test performance between the liquid crystal layer, optical polymer layer or coating layer and the plastic film (PC or PET) in the current new process for laminating the back covers of smart phones and tablets, the preparation method provided by the present invention uses a polyurethane acrylate resin with high adhesion and a blending technology to prepare a UV-curable adhesive with strong adhesion, good versatility and excellent UV aging resistance; at the same time, the preparation method provided by the present invention has a simple process, mild conditions, easy control, and readily available raw materials with low cost, and has broad application prospects.

[0064] The present invention provides a UV-curable adhesive, which is prepared from raw materials including the following components: 30 to 60 parts by weight of polyurethane acrylate; 30 to 50 parts by weight of reactive diluent; 1 to 5 parts by weight of photoinitiator; 5 to 20 parts by weight of special structure oligomer; 1 to 6 parts by weight of coupling agent; 0 to 3 parts by weight of auxiliary agent; the special structure oligomer is selected from one or more of metal polyester acrylate, carboxyl-containing acrylate oligomer, and acrylic acid phosphate. Compared with the prior art, the UV-curable adhesive provided by the present invention adopts specific content components to achieve better overall interaction, and the product has strong adhesion, good versatility, and excellent UV aging resistance.

[0065] In addition, the preparation method provided by the present invention has simple process, mild and easy-to-control conditions, and readily available raw materials with low cost, and has broad application prospects.

[0066] In order to further illustrate the present invention, the following examples are used to provide a detailed description. The raw materials used in the following examples of the present invention are all commercially available products; among them, 1-hydroxycyclohexyl phenyl ketone is provided by CIBA-GEIGY Company, the trade name is Irgacure 184, (2,4,6-trimethylbenzoyl) di(p-tolyl) phosphine oxide is Ficace Ltcure TMO, metal polyester acrylate is Sartomer CN2404, CN2405, carboxyl-containing acrylate oligomer is Sartomer SB500E50, SB510E35, SB520A20, RAHN GENOMER 7151, acrylic acid phosphate is Sartomer CD9050, CD9051, CD9052;

[0067] The polyurethane acrylate is a homemade polyurethane acrylate, and the preparation method is as follows: 85.58 kg of IPDI (Evonik, Covestro, Wanhua) 429.17 kg of IBOA (Sartomer SR506) 0.54 kg of MEHQ (p-hydroxyanisole) (Aladdin) and 0.54 kg of an organic bismuth catalyst (TMG) are sequentially added into a reactor, and a mixed solution of 500 kg of PTMG3000 (BASF) and 16.25 kg of diethylene glycol is added dropwise while stirring, and the dropping speed is adjusted according to the temperature to ensure that the temperature does not exceed 60°C. After the addition is completed, the temperature is kept at 60°C for 2 hours; NCO is detected after 2 hours; NCO reaches the reaction target value between 0.4 and 0.5, otherwise the reaction is continued; after reaching the target value, 16 kg of HEA (Jurong) is added, the temperature is raised to 80°C to start the insulation reaction, and the NCO content is measured every hour after insulation for 2 hours. When the NCO content is less than 0.05%, the reaction is stopped, and the material can be filtered and packaged.

[0068] Table 1 Formula composition of Examples 1 to 5 (wt%)

[0069]

[0070]

[0071] The preparation method is specifically as follows:

[0072] First, add the photoinitiator and active diluent in the set weight proportions in sequence, stir at a low speed of 200 r / min until the photoinitiator is completely dissolved, and then add polyurethane acrylate, special structure oligomer, coupling agent, and auxiliary agent, stir and heat to 50°C, disperse at a high speed of 900 r / min, and then filter to obtain a UV-curing adhesive.

[0073] The various properties of the UV-curable adhesives provided in the above-mentioned Examples 1 to 5 were tested, and the specific use process is as follows:

[0074] (1) Place the prepared UV-curable adhesive into a pressure cooker and connect it to a glue dispenser with a plastic tube, and adjust the glue drop amount; the specific glue drop amount can be adjusted according to the size of the substrate to be bonded and the thickness of the bonding adhesive layer.

[0075] (2) Use a glue dispenser to dispense glue on the edge of the area on the substrate to be bonded, usually in a straight line along the edge of the substrate, and then cover the PC sheet or PET film to be bonded on the surface of the substrate with glue.

[0076] (3) Press the PU rubber roller onto the coated film, and roll it from the end with the glue to the edge of the other end with a predetermined roller pressure and roller speed; wherein the predetermined roller pressure and roller speed can be set and adjusted according to the required thickness of the adhesive film.

[0077] (4) The substrate of the pressed glue and the plastic film are sent to a UV curing machine through a transfer device for UV light curing.

[0078] In the above test, the thickness of the adhesive layer was 20-30 μm, and the UV light curing conditions were: 365 nm mercury lamp light source, exposure energy of 1000-1500 mJ / cm 2 .

[0079] Conventional adhesion test method:

[0080] Cut the bonded materials into test pieces of 25mm×110mm. No bubbles should appear in the test pieces. Fix the test pieces on the tensile test fixture, clamp one end of the diaphragm with a clip, and pull them 180° in the opposite direction at a speed of 300mm / min. When taking the test value, take the average value of the middle stable curve interval as the judgment result.

[0081] Boiling water resistance test method:

[0082] Put the test piece into a constant temperature water bath (pure water at 80℃±5℃) and boil it for 30 minutes, then take it out and wipe off the water stains on the surface with a clean dust-free cloth. After standing at room temperature for 2 hours, check the appearance (the test sample cannot contact the wall of the boiling water container during the water boiling test) and measure the adhesion.

[0083] UV aging test method:

[0084] Using a QUVA weathering tester, the test piece was exposed to UV light from one side of the outer surface of the plastic film; the test lasted for 72 hours and included nine 8-hour cycles (one cycle included 4 hours of UV exposure (UV-A, 340nm, 0.63W / m 2 , 60℃) and 4 hours of humidity condensation (50℃). After the test, the test piece was left to stand at room temperature for 2 hours, then the appearance of the test piece was checked and the adhesion strength was measured; the adhesion peeling force between the substrate and the film was ≥15N and was judged to be OK.

[0085] The test results are shown in Table 2 below.

[0086] Table 2 Adhesive parameters and performance test results of Examples 1 to 5

[0087]

[0088] The experimental results show that, by synthesizing a low-molecular polyurethane acrylate resin, the present invention significantly improves the adhesion of the UV-curing adhesive to the polymer layer, the coating layer and the plastic film in the smartphone back cover bonding process, and the stable UV aging resistance performance; through the blending modification of polyurethane acrylate, the versatility of bonding to various materials is significantly improved. After UV curing, the conventional adhesion between the liquid crystal layer, the optical polymer layer or the coating layer and the plastic film (PC or PET) can reach more than 40N, and the adhesion can reach more than 25N after the UV aging (72h) test.

[0089] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A UV-curable adhesive, prepared from raw materials including the following components: 30 to 60 parts by weight of polyurethane acrylate; 30 to 50 parts by weight of active diluent; 1 to 5 parts by weight of photoinitiator; 5 to 20 parts by weight of special structure oligomer; 1 to 6 parts by weight of coupling agent; Auxiliary agent 0 to 3 parts by weight; The special structure oligomer is selected from one or more of metal polyester acrylate, carboxyl-containing acrylate oligomer, and acrylic phosphate.

2. The UV curing adhesive according to claim 1, characterized in that: The preparation method of the polyurethane acrylate is specifically as follows: IPDI, IBOA, MEHQ and an organic bismuth catalyst are sequentially added into a reaction kettle, and a mixed solution of PTMG3000 and diethylene glycol is added dropwise under stirring, and the dropping speed is adjusted according to the temperature to ensure that the temperature does not exceed 60° C. After the dropping is completed, the temperature is kept at 55° C. to 66° C. for 1 h to 3 h; then NCO is detected, and the reaction target value is reached when NCO is between 0.4 and 0.5, otherwise the reaction is continued; after reaching the reaction target value, HEA is added, and the temperature is raised to 70° C. to 90° C. to start the heat preservation reaction, and after keeping the temperature for 1 h to 3 h, the NCO content is measured every hour, and the reaction is stopped when the NCO content is less than 0.05%, and the discharged material is filtered and packaged to obtain polyurethane acrylate.

3. The UV curing adhesive according to claim 1, characterized in that: The active diluent is selected from one or more of lauryl acrylate, N,N-dimethylacrylamide, cyclotrimethylolpropane formal acrylate, N-vinyl pyrrolidone, ethoxyethoxyethyl acrylate, isobornyl acrylate, and tetrahydrofuran acrylate.

4. The UV curing adhesive according to claim 1, characterized in that: The photoinitiator is selected from one or more of 1-hydroxycyclohexyl phenyl ketone, (2,4,6-trimethylbenzoyl)di(p-tolyl)phosphine oxide, ethyl 2,4,6-trimethylbenzoylphosphonate, and methyl benzoylformate.

5. The UV curing adhesive according to claim 1, characterized in that: The special structure oligomer is metal polyester acrylate, or carboxyl-containing acrylate oligomer, or acrylic acid phosphate, or carboxyl-containing acrylate oligomer and acrylic acid phosphate in a mass ratio of 1:

1.

6. The UV curing adhesive according to claim 1, characterized in that: The coupling agent is selected from silane coupling agent and / or epoxy silane oligomer; the silane coupling agent is selected from one or more of γ-methacryloxypropyltrimethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 1,3,5-tris(trimethoxysilylpropyl)isocyanurate, N-(3-dimethylaminoethyl)-3-aminopropylmethyldimethoxysilane, and N-(piperazineethyl)-3-aminopropylmethyldimethoxysilane; the epoxy silane oligomer is selected from one or more of Maitu MP-200, Aiko Crosile AK200, and Mitsukoshi SY-60.

7. The UV curing adhesive according to claim 1, characterized in that: The auxiliary agent is a light attractant and / or a light stabilizer.

8. A method for preparing the UV-curable adhesive according to any one of claims 1 to 7, comprising the following steps: The photoinitiator and the active diluent are mixed, stirred at a low speed until the photoinitiator is completely dissolved, and then polyurethane acrylate, special structure oligomer, coupling agent and auxiliary agent are added, stirred and heated to 40°C to 60°C, dispersed at a high speed and then filtered to obtain a UV-curing adhesive.

9. The preparation method according to claim 8, characterized in that: The rotation speed of the low-speed stirring is 100 r / min to 300 r / min.

10. The preparation method according to claim 8, characterized in that: The rotation speed of the high-speed dispersion is 800 r / min to 1500 r / min.

Citation Information

Patent Citations

  • Dicing and die attach adhesive

    CN101636462A

  • UV (Ultraviolet) photo-cured adhesive with high bonding strength and preparation method thereof

    CN108384507A

  • High-transmittance LED / UV (Light Emitting Diode / Ultraviolet) curing flame-retardant adhesive and preparation method thereof

    CN115247046A

  • Dicing and die attach adhesive

    US20100056725A1

Cited By

  • Ultraviolet curing adhesive composition for bonding optical composite film and preparation method of ultraviolet curing adhesive composition

    CN121471864A

  • Ultraviolet curing adhesive as well as preparation method, use method and application thereof

    CN121801524A